Photostriction of strontium ruthenate - Tzu-Chiao Wei (Nature Portfolio, 2017)
Light-induced deformation known as photostriction could be used for green energy devices but in most materials the effect is too small to be of practical use. Here, Weiet al. study the photostriction of strontium ruthenate and find photon-induced strain efficiencies of more than one percent.